MAPPING THE DISTRIBUTION OF SEAGRASS IN NIRWANA BEACH, PADANG CITY USING SENTINEL-2 IMAGERY - Sepriani, Nur Astri; Arif, Dian Adhetya; Iswandi, Iswandi; Triyatno, Triyatno (Remote Sensing Technology Study Program, 2023)
Seagrass (Lamun) is a flowering plant (Angiospermae) that thrives in shallow marine environments. Seagrass meadows play a crucial role in aquatic ecosystems, and the degradation or loss of seagrass can impact the balance of these ecosystems. The use of remote sensing technology in mapping the distribution of seagrass beds can support monitoring efforts and contribute to the conservation and protection of marine ecosystems. This research aims to map and measure the extent of seagrass beds in Nirwana Beach, Padang City, in the year 2022. The method employed involves using Sentinel-2A imagery from 2022 and the Object-Based Image Analysis (OBIA) approach for seagrass detection. The Sentinel-2A imagery is processed using ArcGIS and eCognition software, including atmospheric correction, data clipping, composite image creation, segmentation, image classification, and accuracy assessment. The results of processing the Sentinel-2A data in 2022 for Nirwana Beach, Padang City, indicate that seagrass beds are distributed along the Nirwana Beach area, particularly in the eastern and southern regions. The detected seagrass bed covers an approximate area of 25.06 hectares. The use of Sentinel-2A imagery with the OBIA method has proven to be effective in detecting the distribution of seagrass beds in Nirwana Beach, Padang City.